Analisis Manual Material Handling Pada Pekerja Borongan Di PT. JC dengan Metode NBM dan RWL - Mochamad Nuri Affa; Boy Isma Putra (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2017)
PT. JC is a company that uses means of transporting goods to the manual process, or so-called Manual Materials Handling (MMH) is done by workers in the Department of Warehouse. In addition to the process of moving goods by using aids such as forklifts manual removal is still needed in this company because it has advantages compared to using the tool for material removal manually can be done in a limited space. In the process of manual material handling led to several complaints that arise and can be analyzed using a Nordic body map (NBM). The use of nordic body map is an appropriate method to use because by analyzing the map of the body aimed at any part of the body feels pain. Besides complaints can also be known value Recomended Weight Limit (RWL) as recommended by NIOSH (National Institute of Occupational Safety and Health) on estimates possibility of stretching further to the value of Lifting Index (LI) aims to determine the estimated value relative to the voltage level of physical processes manual material handling. From manual material handling processes that cause the symptoms of musculoskeletal disorder completion technically be done to minimize the effects on workers.